Pengaruh Kualitas Produk, Harga dan Desain Kemasan Terhadap Keputusan Pembelian Produk Pop Mie - Rakha Adyatma Budiono; Handy Nur Cahya; Bara Zarreta (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of product quality, price, and packaging design on purchasing decisions for Pop Mie in Semarang City. Pop Mie itself is one of the most popular instant cup noodle products and has a wide market segmentation, especially among productive age people. This research uses quantitative techniques with purposive sampling. The sample in this study amounted to 100 respondents who had bought Pop Mie products at least twice. data collection was carried out by distributing questionnaires via google form. Data analysis using Partial Least Square (PLS) technique with the help of SmartPLS software. The results showed that price and packaging design have a significant influence on purchasing decisions, while product quality has no significant effect. The findings in this study indicate that visual and economic factors are more influential than product quality aspects.